2015
DOI: 10.1371/journal.pone.0138037
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Running Exercise Alleviates Early Progression of Nephropathy with Upregulation of Nitric Oxide Synthases and Suppression of Glycation in Zucker Diabetic Rats

Abstract: Exercise training is known to exert multiple beneficial effects including renal protection in type 2 diabetes mellitus and obesity. However, the mechanisms regulating these actions remain unclear. The present study evaluated the effects of chronic running exercise on the early stage of diabetic nephropathy, focusing on nitric oxide synthase (NOS), oxidative stress and glycation in the kidneys of Zucker diabetic fatty (ZDF) rats. Male ZDF rats (6 weeks old) underwent forced treadmill exercise for 8 weeks (Ex-ZD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 42 publications
6
68
1
2
Order By: Relevance
“…In contrast, NO exhibits various renoprotective effects that counteract the effects of OS. Evidence indicates that impaired NO contributes to the development of DN . In fact, endothelial nitric oxide synthase (eNOS) knockout mice developed DM with progressive nephropathy .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, NO exhibits various renoprotective effects that counteract the effects of OS. Evidence indicates that impaired NO contributes to the development of DN . In fact, endothelial nitric oxide synthase (eNOS) knockout mice developed DM with progressive nephropathy .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ito et al. () found that running exercise improved a reduced formation of nitrate/nitrite metabolites in renal cortex and outer medullar of diabetic Zucker rats. Silva et al.…”
Section: Discussionmentioning
confidence: 99%
“…These results support previous reports in the literature. For example, Ito et al (2015) found that running exercise improved a reduced formation of nitrate/nitrite metabolites in renal cortex and outer medullar of diabetic Zucker rats. Silva et al (2016) reported that treadmill exercise training reversed downregulation of eNOS protein expression in the aorta of high-sugary diet-induced obese mice.…”
Section: Possible Underlying Mechanisms By Which Chronic Voluntary Rumentioning
confidence: 99%
“…An animal study by Ito et al [42], who examined the chronic effects of running in Zucker diabetic fatty rats showed that at early stages of diabetic nephropathy, running beneficially induce alterations in kidney oxidative stress status. More precisely, the 8 weeks running on a treadmill increased NOS activity and protein expression of eNOS and nNOS proteins in the renal cortex of the diabetic rats, suggesting that exercise training may provide renoprotective effects and delay the progression of renal failure at the early stages of diabetic nephropathy [42]. In addition, the renoprotective effects of exercise training have been proved in a study by Tucker et al [43], where the authors compare the effects of high intensity interval training with light intensity exercise training or with a sedentary group of rats.…”
Section: Hemodynamics Changes During Exercise Trainingmentioning
confidence: 99%